Good Bye Lenin! - Wolfgang Becker (2003)
October, 1989 was a bad time to fall into a coma if you lived in East Germany - and this is precisely what happens to Alex's proudly socialist mother. Alex has a big problem on his hands when she suddenly awakens eight months later. Her heart is so weak that any shock might kill her. And what could be more shocking than the fall of the Berlin Wall and the triumph of capitalism in her beloved East Germany? To save his mother, Alex transforms the family apartment into an island of the past, a kind of socialist-era museum where his mother is lovingly duped into believing that nothing has changed. What begins as a little white lie turns into a major scam as Alex's sister and selected neighbors are recruited to maintain the elaborate ruse - and keep her believing that Lenin really did win after all!
Keywords: Comedy, Drama, Romance